Do choosing wisely tools meet criteria for patient decision aids? A descriptive analysis of patient materials. Issue 8 (26th August 2016) - Légaré, France; Hébert, Jessica; Goh, Larissa; Lewis, Krystina B; Leiva Portocarrero, Maria Ester; Robitaille, Hubert; Stacey, Dawn
Abstract : Objectives: Choosing Wisely is a remarkable physician-led campaign to reduce unnecessary or harmful health services. Some of the literature identifies Choosing Wisely as a shared decision-making approach. We evaluated the patient materials developed by Choosing Wisely Canada to determine whether they meet the criteria for shared decision-making tools known as patient decision aids. Design: Descriptive analysis of all Choosing Wisely Canada patient materials. Data source: In May 2015, we selected all Choosing Wisely Canada patient materials from its official website. Main outcomes and measures: Four team members independently extracted characteristics of the English materials using the International Patient Decision Aid Standards (IPDAS) modified 16-item minimum criteria for qualifying and certifying patient decision aids. The research team discussed discrepancies between data extractors and reached a consensus. Descriptive analysis was conducted. Results: Of the 24 patient materials assessed, 12 were about treatments, 11 were about screening and 1 was about prevention. The median score for patient materials using IPDAS criteria was 10/16 (range: 8–11) for screening topics and 6/12 (range: 6–9) for prevention and treatment topics. Commonly missed criteria were stating the decision (21/24 did not), providing balanced information on option benefits/harms (24/24 did not), citing evidence (24/24 did not) and updating policy (24/24 did not). Out of 24 patient materials, only 2 met the 6 IPDAS criteria to qualify as patient decision aids, and neither of these 2 met the 6 certifying criteria. Conclusions: Patient materials developed by Choosing Wisely Canada do not meet the IPDAS minimal qualifying or certifying criteria for patient decision aids. Modifications to the Choosing Wisely Canada patient materials would help to ensure that they qualify as patient decision aids and thus as more effective shared decision-making tools.